Đánh giá tác động của ngập lụt đến sự thay đổi hành vi lựa chọn nhà ở tại Thành phố Hồ Chí Minh - Nguyễn Thị Bích, Hồng; Trương Thành, Hiệp (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The impact of flooding varies among different demographic groups, hence, measuring the effects of flooding on these groups is crucial. The objective is to assess the impact of flooding on various demographic groups, such as poorer/wealthier individuals, those who have/have not lived in flood-prone areas, and differences in their choices of new housing. Utilizing survey data from individual home buyers in Ho Chi Minh City from the third quarter of 2017 to the end of the second quarter of 2018, this study found that overall, flooding significantly negatively affects housing prices. Particularly, the price reduction does not differ significantly among buyer groups, thus attracting those with limited financial resources, as the houses they purchase tend to have lower prices, resulting in a higher proportion of price reduction. This attracts them to higher flood-risk areas. However, buyers who have previously lived in flood-prone areas, despite financial constraints, tend to purchase new homes in non-flooded areas. This suggests a trend where residents undervalue the impact of flooding due to a lack of information.
Keywords: Climate change adaptation; Vulnerability to flooding; Housing market; Housing affordability; Flood experience; Low-income buyers